Brisingr, or, The seven promises of Eragon Shadeslayer and Saphira Bjartskular - Paolini, Christopher (New York : Knopf, 2008)
Eragon tries to uphold the oath he made to save Katrina from King Galbatorix, while being pulled in different directions by the needs of the Varden, elves, and dwarves--all of whom need his help and strength to overcome the tyranny of the king.
Map on endpapers.
Booklist.
Horn Book.
Voice of Youth Advocates (V.O.Y.A.).
Booklist, November 2008.
Horn Book, January 2009.
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Dragons -- Fiction; Fantasy; Magic -- Fiction; Dragons -- Fiction; Magic -- Fiction; Fantastic fiction; Fantastic fiction